Perspectivas sociológicas del quehacer científico. Revisión bibliográfica y enfoques del comportamiento de los investigadores - Nerina Fernanda, Sarthou (Nómadas. Critical Journal of Social and Juridical Science, 2013)
This work is part of a longer range-research project, which aims to explore the process of design and implementation of a public policy instrument that aims to increase the research activity in universities. In this sense, we seek to explore possible explanations of the behavior of researchers, that is to say, what encourages them to do science, and then understand what interpretation of researcher and of science can be sustaining different public policy instruments.
Keywords: scientist; behaviour; sociological view; literature review